Distance teacher education by the Open University of Brazil: democratization and access or massification and commodification of training? (Research, Society and Development, 2021)
This paper aims to discuss the paths taken by teacher training at the Open University of Brazil (UAB) and how much the premises of Distance Education (EaD) and UAB approach or distance from the proposal of access and democratization of education in return to the process of commodification and massification of training. Theses were analyzed in the CAPES Thesis Catalog that dealt with educational policies in the context of UAB between 2006 and 2016, as well as documents and laws dealing with the topic discussed here. We found that the UAB was created with the purpose of meeting the growing demand for teacher training, interiorization, access and democratization of higher public education in the country. However, the model designed for UAB is based on a precarious system of payment of research grants for teachers and tutors and characterized by a process of discontinuity of funding that led the institutions to search for cheaper courses with the adoption of a lower number of tutors, material course and visit to the face-to-face support centers. There was a process of State's lack of responsibility with higher education, transferring responsibility for this training to municipalities and states without the necessary counterpart for an emancipatory training. Thus, the Program was closer to the massive-mercantile model than to democratization.